Community forestry and the stewardship of tropical forests in Asia - Jong, W. de (2002)
A heated debate has been going on for roughly three decades about who should hold stewardship over Asia’s tropical forests. This essay reviews how the debate evolved. Communal forestry advocates like NGOs point out that local groups living in remote corners of countries like Indonesia, Thailand, the Philippines, and India have been managing forests for centuries. They provide examples of successful precolonial communal management practices, which eventually gave way to commercial interests in the late nineteenth century. Postcolonial governments, backed by international organizations, continued to believe in modernist and exploitative forestry practices until the development discourse began to question the impact of economic growth on natural resources and the environment. By the 1980s, the idea emerged of putting local communities back in charge of tropical forests, both for their own livelihoods and the forests’ health. By the 1990s, community forestry coincided with the trend toward decentralization. Unfortunately, the result has often been more exploitation as newly responsible district authorities and village elites seek revenue through timber concessions and oil palm plantations. Despite positive examples—almost 3 million ha under community control in the Philippines—the larger picture is of central authorities reluctant to give up lucrative sources of income. When they do grant local responsibility, it is often over degraded or low quality forests, a burden rather than an asset to local communities. Future agendas must recognize that forests are now of value to a growing number of stakeholders. Local communities may therefore play important roles in restoring forests—if they are compensated—but the complexity of rights and interests suggests that the future lies in co-management. The struggle will shift from who should have control, to how communal stewardship can become feasible and attractive to communities, while meeting the demands of other constituencies.